The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0100-736x2002000200003
|View full text |Cite
|
Sign up to set email alerts
|

Técnica rápida de neutralização viral para a detecção de anticorpos contra o vírus da Diarréia Viral Bovina (BVDV) no leite

Abstract: The identification of bovine viral diarrhea virus (BVDV) positive herds through detection of antibodies in milk may viabilize large scale control/eradication programs. With this objective, the virus neutralization test (VN) was adapted to detect BVDV antibodies in milk. The adaptation consisted of a reduction in the time of incubation followed by detection of viral antigens in the indicator cells by immunofluorescence (IFA) and allowed readings at 24 hours. The rapid virus neutralization test (RVN) was initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…BVD is distributed worldwide, and its seroprevalence is estimated to range between 46% and 78% (RICHTER et al, 2019). In Brazil, several serological studies have demonstrated a wide distribution and high prevalence rate in several states, as follows: Bahia, 56% (NoRoNHA et al, 2001); Paraíba, 39% (FERNANDES et al, 2016); Goiás, 54% (BRITo et al, 2010); Minas Gerais, 61% (MINEo et al, 2006); São Paulo, 56% (SAMARA et al, 2004); Paraná, 61% (AlFIERI et al, 2004); and Rio Grande do Sul, 58% (SCHERER et al, 2002). However, until now, no data were reported for the state of Espírito Santo.…”
Section: Microbiologymentioning
confidence: 99%
“…BVD is distributed worldwide, and its seroprevalence is estimated to range between 46% and 78% (RICHTER et al, 2019). In Brazil, several serological studies have demonstrated a wide distribution and high prevalence rate in several states, as follows: Bahia, 56% (NoRoNHA et al, 2001); Paraíba, 39% (FERNANDES et al, 2016); Goiás, 54% (BRITo et al, 2010); Minas Gerais, 61% (MINEo et al, 2006); São Paulo, 56% (SAMARA et al, 2004); Paraná, 61% (AlFIERI et al, 2004); and Rio Grande do Sul, 58% (SCHERER et al, 2002). However, until now, no data were reported for the state of Espírito Santo.…”
Section: Microbiologymentioning
confidence: 99%